Wydolność tlenowa studentek Śląskiego Uniwersytetu Medycznego w zależności od wieku oraz aktywności fizycznej mierzonej Beep Test – doniesienia wstępne = Aerobic fitness students of Silesian Medical University depending on the age and physical activity Rusing Beep Test- preliminary reports - Mędrak, Anna; Bajerska, Izabela; Plaskacz, Paweł; Łosień, Tomasz (Journal of Education, Health and Sport, 2016)
Mędrak Anna, Bajerska Izabela, Plaskacz Paweł, Łosień Tomasz. Wydolność tlenowa studentek Śląskiego Uniwersytetu Medycznego w zależności od wieku oraz aktywności fizycznej mierzonej Beep Test – doniesienia wstępne = Aerobic fitness students of Silesian Medical University depending on the age and physical activity Rusing Beep Test- preliminary reports. Journal of Education, Health and Sport. 2016;6(7):292-300. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.57819 http://ojs.ukw.edu.pl/index.php/johs/article/view/3662 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 15.06.2016. Revised 09.07.2016. Accepted: 09.07.2016. WYDOLNOŚĆ TLENOWA STUDENTEK ŚLĄSKIEGO UNIWERSYTETU MEDYCZNEGO W ZALEŻNOŚCI OD WIEKU ORAZ AKTYWNOŚCI FIZYCZNEJ MIERZONEJ BEEP TEST – DONIESIENIA WSTĘPNE Aerobic fitness students of Silesian Medical University depending on the age and physical activity Rusing Beep Test- preliminary reports Anna Mędrak, Izabela Bajerska, Paweł Plaskacz, Tomasz Łosień Koło Naukowe Neurorehabilitacji przy Zakładzie Rehabilitacji Leczniczej Katedry Fizjoterapii Śląskiego Uniwersytetu Medycznego w Katowicach STRESZCZENIE Wstęp: Wydolność tlenowa jest to zdolność do podejmowania wysiłku fizycznego, bez znaczących zaburzeń homeostazy w przebiegu procesów utleniania. Tryb życia, warunki środowiskowe oraz gospodarka hormonalna są nieodłącznym elementem warunkującym jej poziom. Podjęcie studiów wpływa na zmianę organizacji życia, co bezpośrednio przekłada się na wydolność organizmu studentek. Uniwersalną metodą badania wydolności aerobowej jest wielostopniowy test wahadłowy – Beep Test. Polega on na utrzymaniu określonego rytmu na dystansie 20 metrów, pomiar jest przerywany, gdy osoba testowana jest niezdolna do dalszego pokonania zadanego odcinka w określonym czasie. Interpretacja uzyskanych wyników odbywa się na podstawie orientacyjnych norm statystycznych. Cel pracy: 1) Czy wiek wpływa na wydolność aerobową studentek? 2) Czy częstotliwość treningów ma wpływ na uzyskane wyniki Beep Test? 3) Czy faza cyklu miesiączkowego wpływa na wydolność tlenową badanej grupy kobiet? Materiały i metody: Zbadanych zostało 65 studentek Śląskiego Uniwersytetu Medycznego w Katowicach w wieku od 18 do 28 lat (x=20,65). W badaniu przeprowadzono Beep Test oraz wykorzystano autorską ankietę, składająca się z 12 pytań, które dotyczyły między innymi: formy, częstotliwości oraz rodzaju aktywności fizycznej, fazy cyklu miesiączkowego, a także subiektywnej oceny wydolności fizycznej. W dwóch pytania użyto skali Likerta. Wyniki i wnioski: Badanie wykazało wzrost wydolności aerobowej kobiet w przedziale wiekowym 18-21 lat.W grupie kobiet, które ukończyły 21 rok życia odnotowano znaczny spadek wyżej wymienionego parametru. Oceniając wyniki według orientacyjnej normy Beep Test dla dorosłych ( Australia), studentki w wieku 18-20 osiągnęły średni wynik na poziomie: słabo,w wieku 21 wynik: przeciętnie, natomiast w przedziale wiekowym 22 wzwyż wynik: słabo. Najlepsze wyniki odnotowano u studentek w fazie folikularnej, natomiast najgorsze w fazie menstruacji. Przyrównując częstotliwość treningów (podaną w ankiecie przez grupę badanych) wraz z jej wzrostem (2-3 razy w tygodniu) zwiększa się wydolność aerobowa. Wśród kobiet trenujących powyżej 4 razy w tygodniu wydolność tlenowa jest widocznie niższa, w tym przypadku otrzymane wyniki Beep Test nie pokryły się z przewidywanym wynikiem ankietowym. Słowa kluczowe: Beep Test, aktywność fizyczna, studentki, wydolność aerobowa SUMMARY Aerobic fitness is the ability to undertake physical activity, without significant disorders of homeostasis in the course of oxidation processes. Life style, environmental conditions and hormonal economy are an integral part of her conditioning level. Beginning of study alters the organization of life which directly translates the physical fitness of students. Universal aerobic capacity test method is a multistage test – Beep test. Interpretation of the results is based on the indicative statistical standards. The aim of the study Does age affect female students aerobic fitness? Is the frequency workouts has an effect on the results obtained Beep Test? Is the phase of the menstrual cycle affects the aerobic fitness test group of women? Material and methods 65 students were examined at the Medical University of Silesia in Katowice in age from 18 to 28 years (x=20.65). The study was conducted Beep Test and author used a questionnaire consisting of 12 questions, which concerned, among other things: the form, frequency and type of physical activity, menstrual cycle phase, as well as subjective evaluation of physical capacity. Two questions used Likert scale. Results and conclusions Research shows an increase in aerobic fitness women between aged 18-21 years. In the group of women who turned 21 life was marked by a significant decrease in the above parameter. Estimating the results by reference standards for Beep Test for adults, students between aged 18-20 has reached the average grade on level: mild, in aged 21 result: average, while people aged 22 and above rating: bad. The best results were noted for students in the follicular phase, while in the worst phase of menstruation. Equating frequency of training (specified in the survey group of subjects), together with its increase (2-3 times per week) increases efficiency stain. Among women who are exercising more than 4 times in a week operability of oxygen is apparently below, in this case, the obtained results Beep Test did not match with the expected result of the questionnaire. Keywords: Beep Test, physical activity, student, aerobic endurance.